German basketball coaches` life satisfaction compared to that of teachers, managers, and the general population: derivatives for sports practice and sustainable education - Wunder, J.; Priem, M.; Wagner, G. G.; Stoll, O. (Journal of Applied Sports Sciences, 2025)
This study investigates the life satisfaction of basketball coaches, addressing a gap in research on sports professionals. Using data from the German Socio-Economic Panel (SOEP), it examines life satisfaction scores among basketball coaches, categorized by license level, and compares them to teachers and managers. While previous research leads to the assumption of above-average life satisfaction of coaches due to specifi c personality characteristics, e.g., higher extraversion and lower neuroticism, the results do not support these suggestions. However, no signifi cant similarities were found between A-license coaches and managers or C-license coaches and teachers. In contrast, both managers and teachers report above-average levels of life satisfaction. Although no signifi cant diff erence between A- and C-license coaches was found, the results indicate that higher license levels can be associated with greater life satisfaction.